Tracking the trajectory of kidney dysfunction in cirrhosis: the acute kidney injury: chronic kidney disease spectrum - Vishnu Girish; Rakhi Maiwall (Clinical and Molecular Hepatology)
Kidney disease in cirrhosis is now viewed as a continuum encompassing acute kidney injury (AKI), acute kidney disease (AKD), and chronic kidney disease (CKD), rather than three different disorders. Contemporary diagnostic criteria for AKI integrate urine output (UO) parameters and acknowledge the intricate relationship and possibility of overlap between functional and structural as well as acute and chronic entities, including hepatorenal syndrome (HRS). AKI demonstrates a propensity for progression to AKD and CKD, particularly in the context of recurrent and severe insults. The diagnostic complexity is further compounded by limitations in serum creatinine measurements, prompting the integration of novel biomarkers and the need to accurately estimate glomerular filtration rate. The diagnosis, phenotyping, and management of AKI should be prompt and early; the initial step should always be volume and UO assessment. A personalized approach is needed and the possibility of co-existing structural or functional kidney disease should be borne in mind. The earlier concept of waiting for 48 hours to diagnose HRS has evolved and early diagnosis and prompt treatment are advised now. Kidney replacement therapy and simultaneous liver and kidney transplantation may be required in resistant cases.